2021
DOI: 10.2147/nss.s320660
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Disordered Breathing, Quality of Sleep and Chronotype in a Cohort of Adult Patients with Bardet–Biedl Syndrome

Abstract: Objective/Background: Bardet-Biedl syndrome (BBS) is a rare but well-recognized ciliopathy with high genetic and phenotypic heterogeneity. Cardinal features include obesity, diabetes and high blood pressure (HBP), which are often associated with sleep-disordered breathing. Also, the high prevalence of blindness due to retinal dystrophy could affect circadian sleep-wake rhythms. We characterized in this cohort of adult BBS patients sleepdisordered breathing, sleep quality, daytime sleepiness and chronotype. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“… 38 Daytime sleepiness is a common symptom in obese patients with OSA, suggesting that objective daytime sleepiness is a more severe type of OSA phenotype with greater sympathetic drive, greater blood pressure, and possibly greater cardiovascular morbidity and mortality. 39 One study of 23 patients revealed that more OSA patients with mild apnea had a morning chronotype, 40 and the process of chronotype change is closely related to the prevalence of OSA. 41 Thus, it might be valuable to identify the chronotype associated with the onset of OSA in adults.…”
Section: Discussionmentioning
confidence: 99%
“… 38 Daytime sleepiness is a common symptom in obese patients with OSA, suggesting that objective daytime sleepiness is a more severe type of OSA phenotype with greater sympathetic drive, greater blood pressure, and possibly greater cardiovascular morbidity and mortality. 39 One study of 23 patients revealed that more OSA patients with mild apnea had a morning chronotype, 40 and the process of chronotype change is closely related to the prevalence of OSA. 41 Thus, it might be valuable to identify the chronotype associated with the onset of OSA in adults.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent observational single-centre study of 30 adults with BBS, 17% had moderate to severe sleep apnoea [19 ▪▪ ]. This study included overnight respiratory polygraphy alongside validated sleep questionnaires.…”
Section: Diabetes Risk Factors In Bardet Biedl Syndromementioning
confidence: 99%
“…Another cardinal symptom is early-onset hyperphagia-associated obesity which starts at preschool age and remains throughout life (13). Obesity in BBS patients contributes to the development of metabolic disorders such as metabolic syndrome, type 2 diabetes, (14,15,16), non-alcoholic fatty liver disease (NAFLD) and liver brosis (26-30%), all of which are related to an increased mortality at adult age (17,18). However, data to what extent liver involvement is secondary to obesity or due to dysfunctional cilia signaling like as in other related ciliopathies such as autosomalrecessive polycystic kidney disease or nephronopthisis remains unclear (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%